Corn oil versus lard: Metabolic effects of omega-3 fatty acids in mice fed obesogenic diets with different fatty acid composition - Pavlisova, Jana; Bardova, Kristina; Stankova, Barbora; Tvrzicka, Eva; Kopecky, Jan; Rossmeisl, Martin (Biochimie, 2016)
Mixed results have been obtained regarding the level of insulin resistance induced by high-fat diets rich in saturated fatty acids (SFA) when compared to those enriched by polyunsaturated fatty acids (PUFA), and how metabolic effects of marine PUFA of n-3 series, i.e. docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), depend on dietary lipid background. Here we compared two high-fat diets, in which the major lipid constituent was based either on SFA in the form of pork lard (LHF diet) or PUFA of n-6 series (Omega-6) as corn oil (cHF diet). Both cHF and LHF parental diets were also supplemented with EPA+DHA (∼30 g/kg diet) to produce cHF+F and LHF+F diet, respectively. Male C57BL/6N mice were fed the experimental diets for 8 weeks. Insulin sensitivity was assessed by hyperinsulinemic-euglycemic clamps in mice fed LHF and cHF diets, and then metabolic effects of cHF+F and LHF+F diets were assessed focusing on the liver and epididymal white adipose tissue (eWAT). Both LHF and cHF induced comparable weight gain and the level of insulin resistance, however LHF-fed mice showed increased hepatic steatosis associated with elevated activity of stearoyl-CoA desaturase-1 (SCD1), and lower plasma triacylglycerol levels when compared to cHF. Despite lowering hepatic SCD1 activity, which was concomitant with reduced hepatic steatosis reaching the level observed in cHF+F mice, LHF+F did not decrease adiposity and the weight of eWAT, and rather further impaired insulin sensitivity relative to cHF+F, that tended to improve it. In conclusion, high-fat diets containing as much as ∼35 weight% as lipids induce similar weight gain and impairment of insulin sensitivity irrespective whether they are based on SFA or Omega-6. Although the SFA-rich diet containing EPA+DHA efficiently reduced hepatic steatosis, it did so without a corresponding improvement in insulin sensitivity and in the absence of effect on adiposity.
Keywords: Insulin Resistance; Stearoyl-CoA desaturase-1; kukuřičný olej; Fatty Acids, Omega-3; omega-3 mastné kyseliny; Obesity; kyseliny mastné omega-6; Insulin resistance; dietní tuky; myši; Mice; inzulinová rezistence; tuková tkáň; ztučnělá játra; mužské pohlaví; Adipose Tissue; zvířata; Omega-3 fatty acids; Animals; Corn Oil; Fatty Liver; Male; Fatty Acids, Omega-6; Hepatic steatosis; Dietary Fats